Surgery of temporomandibular joint under local anaesthesia - Gajiwala J. Kalpesh (Indian Journal of Plastic Surgery)
Temporomandibular joint ankylosis is a debilitating disorder arising from an inability to open the mouth. This leads to poor nutrition, poor dental hygiene, and stunted growth. Anaesthesia, especially general anaesthesia, is very difficult to administer. There is a lack of direct visualization of the vocal cords, tongue fall following relaxation, and an already narrowed passage due to a small mandible, which makes even the blind nasal intubation difficult. There are various techniques described in literature to overcome these challenges, failing which, one needs to do tracheostomy. All the risks of difficult intubation and general anaesthesia can be avoided if the surgery is done under local anaesthesia. A simple but effective method of successful local anaesthesia is described, which allows successful temporomandibular joint reconstruction.